An investigation into the effect of backup coat sands on investment casting products - Kaila, Vishal N; Dave, Indravadan B. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Investment casting is a well-known method for producing precise and finished products. The shell-making process takes a long time and consumes a large amount of coating sands. On the wax pattern tree, the ceramic coating sands are used as a primary coat and several backup coats. Zirconia sand is used for primary coating on a shell in this work. Backup coat sands are made up of fused silica and alumina silica. Colloidal silica is used as a binding material in the formation of all shells. In the work, the effect of fused silica and alumina-silica sand as a backup coat on casting properties was determined. The experimental work evaluated casing properties such as microstructures, grain size measurement, gas porosity, and shrinkages. On the dried, de-waxed, and fired shell, the porosity of the shell mold was determined for the permeability level. Alumina-silica sand has a porosity of 27 to 31 percent, whereas fused silica has a porosity of 22 to 25 percent. It produces better casting properties in alumina–silica casting products than fused silica. Casting grain sizes range from 22 to 38 microns. The grain size of alumina-silica casting is finer than that of fused silica shell casting. Gas porosity and shrinkage in the casting were found to be moderate in all castings.